2004
DOI: 10.1074/jbc.m310185200
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Zinc Finger Motifs in the Leishmania tarentolae LC-4 (=TbMP63) L-complex Editing Protein Affects the Stability of the L-complex

Abstract: The uridine insertion/deletion editing complex, which we have termed the L-complex, is composed of at least 16 polypeptides stabilized entirely by protein-protein interactions. Three L-complex proteins contain zinc finger motifs that could be involved in these interactions. In Leishmania these proteins are labeled LC-1, LC-4, and LC-7b, and the orthologs in Trypanosoma brucei are labeled MP81, MP63, and MP42. Overexpression of TAPtagged LC-4 in Leishmania tarentolae led to a partial localization of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…2C). This confirms previous studies that showed their interaction in vivo and in vitro Kang et al 2004), and shows that the mutations did not affect their interaction. A small amount of the KREX2 proteins was nonspecifically immunoprecipitated, i.e., in the absence of KREPA2.…”
Section: Trypanosoma Brucei Krex1 and Krex2 Are Exouasessupporting
confidence: 81%
See 1 more Smart Citation
“…2C). This confirms previous studies that showed their interaction in vivo and in vitro Kang et al 2004), and shows that the mutations did not affect their interaction. A small amount of the KREX2 proteins was nonspecifically immunoprecipitated, i.e., in the absence of KREPA2.…”
Section: Trypanosoma Brucei Krex1 and Krex2 Are Exouasessupporting
confidence: 81%
“…The difference between these results probably reflects the larger amounts of the enzymes used in the previous studies than with the in vitro transcribed/translated proteins described here, although differences in the dsRNA substrate and/or assay conditions cannot be excluded. Nevertheless, interaction of KREX2 with its binding partner KREPA2 Kang et al 2004) resulted in efficient removal of Us from both ssRNA and the dsRNA ( Fig. 2; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The REL1-TAP pull-down showed a minor amount of the endogenous REL1 in addition to the tagged REL1 (14). Similar results were obtained for another component of the REL1 subcomplex-the LC4 (MP63) protein (17). These results suggest that there is a minor percentage of the REL1 subcomplexes that are dimeric, but the majority are single-copy.…”
supporting
confidence: 73%
“…This is consistent with coimmunoprecipitation experiments using recombinant protein, which showed that mutating the KREPA2 zinc fingers did not affect pulldown of KREL1 (data not shown). Interestingly, expression of LtKREPA2 with disrupted zinc fingers in Leishmania resulted in substantial breakdown of the 20S editosome (54), suggesting that these motifs do have a functional role, possibly in interaction with KREX2 or perhaps in proper folding of KREPA2 itself. The latter would be consistent with the finding that correct folding of recombinant KREPA3, which also contains two zinc finger motifs, required zinc ions (47).…”
Section: Discussionmentioning
confidence: 99%